Efektivitas Metode Pembelajaran Berbasis TIK pada Mata Pelajaran Pekerjaan Dasar Elektromekanik - Effendi, Hansi; Muskhir, Mukhlidi; Rahmat, Roni Eka (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
Student-centered learning and using media and ways that are suitable for the students and using the right technology will make learning more fun. This study aims to look at the effectiveness of Information and Communication Technology (ICT)-based learning in Electromechanical Basic Work (EBW) subjects at SMK Muhammadiyah 1 Padang. This study used a pre-experimental method with one group pretest-posttest design applied to class X TITL A as an experimental class. Data collection was carried out using an objective test with a total of 20 questions. Data were analyzed using classical completeness and gain scores to see the effectiveness of applying ICT-based learning methods. Based on the results of the study, almost all students completed their learning and there was an increase in student learning outcomes in the large category. Thus the application of ICT-based learning methods effectively applied to EBW subjects in class X TITL A SMK Muhammadiyah 1 Padang.